Prior Consultation in Sarayaku (Ecuador): Criminal Implications and Restorative Justice in Integral Reparation - Maldonado Erazo, Ximena Elizabeth; Santillán Montenegro, Leslie Fernanda (Ius Humani. Jornal do direito, 2026)
This research analyzed the right to prior, free, and informed consultation of the Kichwa people of Sarayaku, based on the judgment issued by the Inter-American Court of Human Rights in the case Sarayaku v. Ecuador. The objective was to examine the scope of the Inter-American standard on prior consultation and its application within the Ecuadorian legal system, through a comparative analysis of the rights of Indigenous peoples and communities recognized in the 1978 Constitution, codified in 1993 and reformed in 1996, as well as in the 1998 and 2008 Constitutions. The study adopted a qualitative approach, grounded in a documentary review of the national and international legal framework and Inter-American jurisprudence concerning participation rights, Indigenous collective rights, and the rights of nature in the context of the exploitation of non-renewable natural resources. The findings revealed that, despite the formal recognition of prior consultation within the Ecuadorian constitutional system, significant challenges persist in its effective implementation in Indigenous territories affected by extractive activities. Additionally, the analysis incorporated a criminal law perspective to assess the legal implications of damage to Indigenous territory and the environment as collective legal interests, as well as the comprehensive reparation measures ordered by the Inter-American Court from a restorative justice perspective. It was concluded that the effectiveness of prior consultation remains limited in practice and in the materialization of comprehensive reparation measures for affected communities.